Case report: Reversible punctate inflammatory foci in the corpus callosum: A novel radiological finding of CAR T-cell therapy-related neurotoxicity - Pensato, Umberto; de Philippis, Chiara; Pistolese, Flavio; Mannina, Daniele; Marcheselli, Simona; Politi, Letterio S.; Santoro, Armando; Bramanti, Stefania (Frontiers in Neurology, 2023)
Introduction Chimeric antigen receptor T-cell therapy-related neurotoxicity is a novel cytokine-mediated neurological syndrome that may present with a broad spectrum of manifestations. Descriptions of novel distinctive features are pivotal to untangling this condition's clinical and instrumental signature in order to inform diagnosis and pathophysiology. Case A 27-year-old female patient received anti-CD19 CAR T cells for a refractory primary mediastinal B-cell lymphoma. At 6 days after the infusion, she developed mild ideo-motor slowing, dysgraphia, and drowsiness. Despite specific treatment with dexamethasone, her neurological status progressively worsened to a comatose state within 24 h. EEG and CSF analyses were non-specific, showing background slowing and inflammatory findings. Brain MRI revealed multiple focal punctate areas of T2-weighted hyperintensity localized in the body and isthmus of the corpus callosum. Following the administration of high-dose intravenous methylprednisolone, her neurological status resolved within 48 h. Notably, the follow-up brain MRI did not reveal any abnormalities in the corpus callosum, except for a reduction of fractional anisotropy. Conclusion Reversible punctate inflammatory foci of the body and isthmus of the corpus callosum may represent a novel radiological finding of CAR T-cell therapy-related neurotoxicity.